Involving national stakeholders in a systems approach to map drivers of childhood obesity and actions to prevent childhood obesity in Denmark: the Generation Healthy Kids Study - Knud Ryom; Paul Bloch; Ulla Toft; Didde Høeg; Louise T. Thomsen; Steven Allender; Harry Rutter; Adrian Bauman; Rikke Fredenslund Krølner; Anders Blædel Gottlieb Hansen (Health Research Policy and Systems)
Abstract Background Childhood obesity is a preventable global public health challenge, increasingly recognized as a complex problem, stemming from complex drivers. Obesity is characterized by multiple interdependencies and diverse influences at different societal levels. Tackling childhood obesity calls for a holistic approach that engages with complexity and recognizes that there is no single “magic bullet” intervention to prevent obesity. To facilitate a shared understanding of the complex structures and relationships that determine children’s weight development, systems approaches have shown promising potential. However, systems approaches require more development and research in public health. Aim This paper describes the processes of gathering national stakeholders to create a system map of childhood obesity drivers in Denmark to map existing obesity prevention initiatives and define real-world actions to prevent childhood obesity in local communities in Denmark. The system map and action ideas will inform the development of community-based activities in a large-scale national study, the Generation Healthy Kids Study. Methods During two workshops in the autumn of 2022, national stakeholders (n = 45) were involved in generating and revising a system map. We used a scripted approach inspired by group model building and community-based systems dynamics methods to engage stakeholders, collect and visualize their knowledge on childhood obesity, create consensus on the drivers of childhood health, identify local and national intervention opportunities for prevention of childhood obesity and develop actions to create system changes. Results The study identified the following six sub-systems of factors influencing childhood obesity: (1) family; (2) diet and dietary habits; (3) physical activity and active living; (4) mental health and wellbeing; (5) screen, media and sleep; and (6) competencies of professionals. Conclusions A systems approach to childhood obesity was useful to generate a shared understanding of the underlying drivers of childhood overweight and obesity and has potential for informing initiatives at local and national level in Denmark. However, challenges were experienced regarding the usefulness of the system mapping process, with a tension between the map as a step in a shared process towards actions and the map as means to gain a deeper understanding of the complex system of childhood overweight and obesity and how to change the system.